Knowledge, attitude, and practices of pregnant women towards antenatal care in Rural health training centre in Achrol, Jaipur, Rajasthan - Devi, Bachaspatimayum Anuradha; Mathur, Roopali Nath; Sisodia, Gejendra Singh; Manohar, Ravindra Kumar; Gite, Amol Rajender; Bharadwaj, Manish Kumar (International Journal Of Community Medicine And Public Health, 2022)
Background: Pregnancy and child birth are important stages in a woman’s life. During pregnancy, both the mother and their unborn babies face health problems which can lead to complications. Prevention of these complications can be possible only when all pregnancies are monitored by skilled care providers. Methods: In this study, it refers to a pregnant women’s understanding of components of antenatal care which include registration of pregnancy, danger signs during pregnancy etc. Attitudes are emotional, motivational, perceptive and cognitive beliefs that positively or negatively influence the behaviour or practice of an individual. The study was designed as a cross sectional study. Study population were pregnant females attending antenatal clinic in a rural health training centre. Results: A total of 150 pregnant women completed the study maximum are multigravida. The age distribution depicted in current study shows maximum participants are from the age group of 21-24,maximum participants are 10th pass and are not working staying in the joined family of own house. Knowledge of pregnant women about antenatal care are ideally ANC visit was 4-6 times as per participants and minimum was 2 visits as revealed in study results. Practice of pregnant women on ANC care shows minimum participant registered in first trimester. Attitude of pregnant women about ANC showed maximum of pregnant women exhibited positive attitude towards necessary to register ANC check-up and also Institutional delivery and danger sign. Conclusions: The knowledge and awareness regarding importance of ANC is the need of this era it also help to reduce mortality rate. To improve community awareness on ANC community campaign and mass media should use.